FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF - Yuyun Naelufar; Anita Wijayanti; Rosa Nikmatul Fajri (ITB AAS INDONESIA, 2021)
The purpose of this study was to iexamine and analyze the effect of EPS, ROE, PER, inflation and interest rates on stock prices of manufacturing companies in the automotive sub-sector listed on the Indonesian Stock Exchange. The sample of this research is the automotive sub-sector manufacturing companies ilisted on the Indonesia Stock Exchange during 2016-2019. The samples this study were 9 companies with total of 36 dats. The sampling technique used purposive side. The data analysis methode used in this study is multiple linear regresion analiysis using SPSS 21 software’s. The result showed that the effect of EPS, ROE, PER, inflationiand interes rates has a effect on stocke prices by 80.3% and the remaining 19.7. % influencedi by other factor not examined. From the partial test, EPS has an effeck on stocks prices, while the variables ROE, PER, inflation and interest rates have no effection stock prices. Keywords: EPS, ROE, PER, Inflation, Interest Rates, Stock Prices